2013
DOI: 10.1016/j.bpj.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

RPA-Mediated Unfolding of Systematically Varying G-Quadruplex Structures

Abstract: G-quadruplex (GQ) is a noncanonical nucleic acid structure that is formed by guanine rich sequences. Unless it is destabilized by proteins such as replication protein A (RPA), GQ could interfere with DNA metabolic functions, such as replication or repair. We studied RPA-mediated GQ unfolding using single-molecule FRET on two groups of GQ structures that have different loop lengths and different numbers of G-tetrad layers. We observed a linear increase in the steady-state stability of the GQ against RPA-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 50 publications
(57 reference statements)
2
70
1
Order By: Relevance
“…Another aspect of RECQ5-mediated GQ unfolding is whether this weak activity might be adequate due to a cooperation of RECQ5 with RPA, which is known to significantly enhance RECQ5's helicase activity by inhibiting RECQ5's strand annealing activity (22). RPA has been demonstrated to be a potent GQ destabilizer (38) and cooperation between RPA and RECQ5 might eliminate the need for RECQ5 to be efficient at destabilizing these structures. Second, we note that the BLM construct used for this comparison was a functional core of full-length protein and contains helicase, RQC, and Helicase and RNase D-like C-terminal (HRDC) domains.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of RECQ5-mediated GQ unfolding is whether this weak activity might be adequate due to a cooperation of RECQ5 with RPA, which is known to significantly enhance RECQ5's helicase activity by inhibiting RECQ5's strand annealing activity (22). RPA has been demonstrated to be a potent GQ destabilizer (38) and cooperation between RPA and RECQ5 might eliminate the need for RECQ5 to be efficient at destabilizing these structures. Second, we note that the BLM construct used for this comparison was a functional core of full-length protein and contains helicase, RQC, and Helicase and RNase D-like C-terminal (HRDC) domains.…”
Section: Discussionmentioning
confidence: 99%
“…The gamma parameter, obtained from a ratio of the intensity change in acceptor and donor intensities upon acceptor photobleaching, revealed the underlying mechanism of the shifting of the F1 and F2 peaks as POT1 is titrated in the 0-200 nM range ( Fig. S5) (29). We interpret the changes in the gamma parameter to be due to POT1 loading to the TTAG overhang, which spaces the donor away from the GQ.…”
Section: Pot1mentioning
confidence: 99%
“…Force spectroscopy measurements have shown that the end to end distance change upon unfolding of a GQ is in the ~ 1 nm range (You et al 2015). Therefore, it is possible to monitor GQ dynamics by smFRET in isolation (Ying et al 2003; Lee et al 2005; Shirude and Balasubramanian 2008; Okumus and Ha 2010; Kruger and Birkedal 2013; Long and Stone 2013; Tippana et al 2014) or while it interacts with single stranded DNA binding proteins (Kruger et al 2010; Hwang et al 2012; Qureshi et al 2012; Ray et al 2013; Hwang et al 2014; Ray et al 2014; Zhou et al 2014), helicases (Budhathoki et al 2014; Chatterjee et al 2014; Zhou et al 2014; Budhathoki et al 2015), or GQ-stabilizing small molecules (Jena et al 2009; Kreig et al 2015). Furthermore, monitoring more subtle features, such as different conformations of GQ, is also possible with carefully designed DNA constructs (Long and Stone 2013; Budhathoki et al 2015).…”
Section: Introductionmentioning
confidence: 99%